A busca da competitividade pela formação de rede de empresas: um estudo na Central Mais Supermercados - Ribeiro, Claudete Fogliato; Baisch, Lindiane da Veiga; Camfield, Luis Henrique Ramos (Revista Gestão da Produção Operações e Sistemas, 2006)
The establishment of a company network represents an important business strategy to promote development and competitive advantages. The economy globalization and its effects, mainly related to the technology advances and the stimulating competition, force the companies towards the search for innovations and new administrative methods. It is believed that such study is relevant, because of its recency thus requiring a deeper knowledge by the academic and business areas. This paper attempted to present in-depth theoretical knowledge through a critical analysis, diagnosing the businessmens perception regarding the achived results after integrating a company network. As a study method, an exploratory research was utilized, consisting of bibliographical and field survey. This study also allowed for the identification and analysis on the main advantages, customers satisfaction and dissatisfaction along with the development of the operational activities of Central Mais Supermarket, located in the city of Santa Maria, Brazil. The paper highlights the importance of the establishment of the Company Network as a competitive, surviving and alternative strategy, so that the supermarket business can operate in the economic and social aspects, reducing its costs and offering quality services and products, reaching more new customers. Keywords: Company Network; Competitiveness; Strategy.